Covid-19 and the Impact on Pensions and Retirement Strategies of Urban Workers in China: A Thematic Analysis - Wang, Qi; Émon, Ayeshah (Journal of Education Culture and Society, 2025)
Aim. This study examines the experiences, expectations, and expressed future plans of urban workers in their middle age in China covered by the Enterprise Employee Basic Pension. Methods. We conducted 33 semi-structured in-depth qualitative interviews with middle-aged workers in urban regions within the public and private sectors in mainland China to thematically examine the connections between their feelings, experiences, plans, and actions around retirement in the aftermath of Covid-19, and how they perceived the Chinese government’s retirement and pension policies. Results. Our findings show that the Covid-19 pandemic contributed to a significant level of anxiety, distrust of public policy, and a preoccupation with self-reliance, health, and finances. Participants who were worried about their health but felt financially stable considered opting for earlier retirement. Those that felt financially insecure felt compelled to extend their working lives, demonstrating a need for greater self-sufficiency, and less reliance on social welfare schemes. Conclusions. These insights underscore the need for addressing post-pandemic vulnerabilities and further policy reforms to bolster fairness and public trust towards the social security system.